The EPPO/OLAF compendium of national procedures: Croatia - Hauck, Pierre; Schneider, Jan-Martin; Justus Liebig University Giessen (My University, 2025)
This Croatian EPPO/OLAF volume discusses the Croatian laws relevant to European Public Prosecutor's Office (EPPO) investigations of EU fraud in Croatia. It covers EPPO procedures in Croatia, practical examples, EU fraud typologies, criminological findings and relevant case law. The volume also introduces criminal financial law in fraud cases and discusses the key defenses that must be protected in EPPO proceedings. The second part summarizes the provisions governing OLAF investigations in Croatia, with a focus on external investigations under Regulation 2020/2223.
Keywords: ddc:340; ddc:320